Iron(III)-porphyrin immobilized on mesoporous A1-MCM-41 and polymethacrylic acid as catalysts for the single-step synthesis of phenol from benzene - Hamid, Helda (2005)
Mesoporous molecular sieve Al-MCM-41 with Si/Al=20 and polymethacrylic acid (PMAA) were used as supports for the immobilization of bulky iron(III)- 5,10,15,20-tetra-(4-pyridyl) porphyrin (Fe-TPyP). Metalloporphyrin of Fe(III) was encapsulated inside the mesopores of the ordered structure of Al-MCM-41 by sequential synthesis of Fe-TPyP via treatment of FeCl3 with 5,10,15,20-tetra-(4- pyridyl) porphyrin (TPyP), followed by encapsulation of Fe-TPyP. Fe-TPyP complexes were also successfully encapsulated into PMAA by polymerizing methacrylic acid (MAA) with a cross-linker around the Fe-TPyP complexes. The materials obtained were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Ultraviolet Visible Diffuse Reflectance (UV-Vis DR), Electron Spin Resonance (ESR), Luminescence and 13C CP/MAS NMR spectroscopies, Thermogravimetric Analysis (TGA) and elemental analysis. The powder XRD data confirmed that the ordered structure of mesoporous Al-MCM-41 remained intact after encapsulation process. Characterization of Fe-TPyP composite with Al-MCM-41 and PMAA using FTIR, UV-Vis DR and ESR confirmed that the structure of Fe-TPyP in inorganic and polymer supports is similar with bare Fe-TPyP. The specific interaction of Fe-TPyP in Al-MCM-41 and/or PMAA was studied by ESR, 13C CP/MAS NMR and Luminescence spectroscopies. The ESR spectra of Fe-TPyP/Al-MCM-41 and Fe-TPyP/PMAA composites showed that there is a shift towards a higher g-value confirming the interaction between Fe-TPyP and supports is occurred. By quenching of the luminescence spectra of Fe-TPyP/PMAA with various concentration of Fe-TPyP, it is evidenced that there is some interaction between Fe-TPyP and PMAA. Further evidence of interaction was corroborated by 13C CP/MAS NMR spectra with show that the peak of carboxyl of PMAA is shifted to higher magnetic field. Single-point BET surface area analysis was used to determine specific surface area of the composites. It is revealed that the surface area of Fe-TPyP/Al-MCM-41 composites is decreased with an increase in Fe-TPyP, suggesting the encapsulation of the complex in the pores of Al-MCM-41 has been achieved. With mesoporous molecular sieve (Al-MCM-41) and the polymer (PMAA) as supports, the immobilized iron-porphyrin system has demonstrated excellent activity for the single-step synthesis of phenol from benzene under mild reaction conditions. The effect of reaction time, solvent, amount of Fe-TPyP loading, temperature and the performance of the recovered catalysts have been studied. The immobilized iron-porphyrin in PMAA (Fe-TPyP/PMAA) gives a higher activity compared to Fe-TPyP supported on Al-MCM-41 (Fe-TPyP/Al-MCM-41). However, the product selectivity of Fe-TPyP/PMAA is not as good as that of Fe-TPyP/ Al-MCM-41. Thus, it is reasonable to assume that the hydrophobic nature of Fe-TPyP/PMAA would account for the high activity, while the rigid, ordered structure of Fe-TPyP/Al-MCM-41 would contribute towards the high selectivity in the single-step synthesis of phenol from benzene in the present study.